Lost in implementation: NSW police force crime prevention officer perspectives on crime prevention through environmental design - Clancey, Garner (Crime prevention and community safety, 2018)
Crime prevention through environmental design (CPTED) is practiced by various professions and agencies in many jurisdictions. The role police play in CPTED has received limited scrutiny from academics within Australia (and other countries). This article makes an important contribution to addressing this gap in the literature through providing New South Wales Police Force Crime Prevention Officers (CPOs) perspectives on their role in reviewing council development applications from a CPTED perspective. Findings show police-council relations vary considerably. Some police-council areas have clear policies in place to enable police to contribute to reviewing crime risks of development applications, whilst others do not. Many police feel their engagement in the planning and development process is often tokenistic, receiving limited feedback from councils about their recommendations. For these police, they see little ongoing relevance of reviewing development applications. If police are to remain involved, there is a need to develop clearer parameters of how police will contribute and what they can realistically be expected to contribute to this process.